Long-term impact of pregnancy-related venous thrombosis on quality-of-life, general health and functioning: results of a cross-sectional, case–control study. Issue 6 (8th November 2012) - Wik, Hilde Skuterud; Jacobsen, Anne Flem; Sandvik, L; Sandset, P M
Abstract : Objectives: To evaluate the long-term consequences of pregnancy-related venous thrombosis (VT) by the assessment of generic quality-of-life (QOL), well-being, general health and daily-life functioning. We also wanted to evaluate the impact of the frequently occurring complication post-thrombotic syndrome (PTS) after that of deep vein thrombosis (DVT). Design: Population-based cross-sectional, case–control study. Setting: 18 Norwegian hospitals during 1990–2003. Participants: The study population comprised 559 cases with a validated first-ever, pregnancy-related VT and 1229 controls naïve for VT at the time of index pregnancy. Cases were identified using the Norwegian Patient Register and the Medical Birth Registry of Norway and the latter was used to select as controls women who gave birth at the same time as a case. After exclusion of two cases with missing location of VT, the final study population comprised 311 cases and 353 controls. Methods: Self-completion of a comprehensive questionnaire in 2006. Main outcome measures: Generic QOL and well-being assessed by the Ferrans and Powers QOL Index (QLI) and the General Health Questionnaire (GHQ-20). Results: QOL assessed by QLI did not differ between cases and controls; mean score 23.1 (95% CI 22.7 to 23.5) vs 23.7 (23.3 to 24.0), neither did well being assessed by GHQ-20; 18.7 (18.0 to 19.4) vs 17.9 (17.3 to 18.4). However, cases reported pain other than in the lower limbs and muscle–skeletal problems more often and were more often physically worn out after work compared with controls. Cases which developed PTS reported poorer health, had pain more often, developed skin and psychiatric problems, used analgesic drugs more frequently and were more often on sick leave as compared to those without PTS. Conclusions: Long-term generic QOL and subjective well-being 3–16 years after a pregnancy-related VT were not different from a reference population, but women with PTS after DVT seemed to have poorer QOL and an impaired general health.